Beziehungen zwischen Oberflächengestalt, Klima und Vegetation von Nord-Transvaal - Schmidt-Eisenlohr, Wilhelm F. (ERDKUNDE, 1967)
The interdependence of geomorphological, climatic and vegetation factors is shown by examples found in the northern part of South Africa. The high ridge of the Soutpansberg, which runs from west to east, significantly divides the low Limpopo Valley in the north from the high veld of Pietersburg in the south. The latter is bordered by the Great Escarpment in the east, which is the result of cyclic lifting and erosion of the continent, influenced by climatic conditions. Inselberge are another result of arid or semi-arid effects. Within a small zone around them, favourable underground water conditions allow plant growth and consequently settlement; this is in contrast to the generally dry ground all round. Climatic data gathered at the author's residence west of Messina show up the particular situation within the semi arid bush of this periodically humid tropical area. The Soutpansberg as well as the Escarpment receives higher precipitation caused by humid air from the Indian Ocean. The Lowveld at the base of the Escarpment behaves in a similar way to the Limpopo Valley. The very hot and humid tropical climate of the neighbouring low plains of Mozambique just touches the Northern Transvaal. Both river systems and run-off must have changed during previous geological time. Recent river beds are mostly dry (rivier) and spruits are typical of this region. But occasionally torrents caused by heavy rainfall rush down the riverbeds for a few hours. In January 1958 a number of heavy rains had catastrophic consequences, especially by destroying roads. Weathering, soil formation and groundwater are intimately connected with the climatic conditions. Calcrete and magnicrete as incrustations at the surface are typical secondary formations within areas of low rainfall under this climate. The vegetation type is also due to the semi-arid climate. Apart from the river beds, only the mountainous and humid regions show a special flora. The vegetation of the Bushveld and Lowveld areas is not uniform, but shows variations and transitions within narrow distances. Some of the most characteristic plants are described in relation to edaphic, geomorphologie and climatic conditions. The abundance of Baobabs in the Limpopo Valley and Messina area is remarkable and therefore their distribution and manner of growth are discussed in particular. Another typical bush-plant is the Mopane. Furthermore, other succulents such as aloes, euphorbiae etc. (the original hearth area of which is South Africa) are described. Human influence and cultivation have changed some natural features of vegetation and have partly destroyed the natural balance. All in all, the natural scenery is still similar to the original one in this vast, thinly populated area. Only within an island-like area around Messina with its copper mines have conditions strongly changed.